The Flint Quarry of Pozarrate (Treviño, Spain) in the Context of Iberian and Early European Neolithic Mining - Tarriño, Antonio; Elorrieta, Irantzu; Alonso-Herrero, Diego; López-Tascón, Cristina; Hernández-Hernández, Hugo; Castañeda, Nuria; Larreina, David; Aguirre, Mikel; Mujika, José Antonio (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2022)
This paper presents the current state of research on the Early Neolithic flint quarry of Pozarrate (Treviño, Burgos) in the north of Spain. This site is part of the Prehistoric Flint Mining Complex of Treviño. The geological features of the territory made it a suitable place for the exploitation of the Treviño flint since Paleolithic times, especially during the Neolithic. Recent research at the site has revealed interesting findings, such as antler and dolerite mining equipment and different flint tools, among other recoveries. Radiocarbon dates indicate an Early Neolithic activity which makes Pozarrate one of the few flint procurement sites in the Iberian Peninsula from this period. Moreover, a considerable number of elements link Pozarrate to the Early European Neolithic flint mining phenomenon.
il. ; 24 cm
Keywords: archeologia -- czasopisma; Treviño Flint; Prehistoric Mining; Neolithic; Iberian Peninsula

La civilisation énéolithique dans la péninsule ibérique, Nils Aberg, Uppsala, 1922 : [recenzja] - Kostrzewski, Józef (1885–1969) (Polskie Towarzystwo Prehistoryczne, 1923)
29 cm
Keywords: eneolit -- Półwysep Iberyjski; eneolitu kultury; społeczności eneolitu; megality neolitu; przedmioty krzemienne neolitu